Gravel bars are sites of increased CO2 outgassing in stream corridors. Issue 1 (December 2017) - Boodoo, Kyle; Trauth, Nico; Schmidt, Christian; Schelker, Jakob; Battin, Tom
Abstract Streams are significant sources of CO2 to the atmosphere. Estimates of CO2 evasion fluxes (f CO2 ) from streams typically relate to the free flowing water but exclude geomorphological structures within the stream corridor. We found that gravel bars (GBs) are important sources of CO2 to the atmosphere, with on average more than twice as highf CO2 as those from the streamwater, affectingf CO2 at the level of entire headwater networks. Vertical temperature gradients resulting from the interplay between advective heat transfer and mixing with groundwater within GBs explained the observed variation inf CO2 from the GBs reasonably well. We propose that increased temperatures and their gradients within GBs exposed to solar radiation stimulate heterotrophic metabolism therein and facilitate the venting of CO2 from external sources (e.g. downwelling streamwater, groundwater) within GBs. Our study shows that GBf CO2 increasedf CO2 from stream corridors by [median, (95% confidence interval)] 16.69%, (15.85–18.49%); 30.44%, (30.40–34.68%) and 2.92%, (2.90–3.0%), for 3rd, 4th and 5th order streams, respectively. These findings shed new light on regional estimates off CO2 from streams, and are relevant given that streamwater thermal regimes change owing to global warming and human alteration of stream corridors.